The education concept from the perspective of K.H. Muhammad Zaini bin Abdul Ghani and its relevance to contemporary islamic education - Azhari, Ahmad; Saputra, Hadi; Jamilah, Jamilah; Barizi, Ahmad (Universitas Ahmad Dahlan, 2023)
Innovation in Islamic education needs to be implemented today, considering that Islamic education is oriented to improving generations of Muslims, which will help to overcome the moral problems of the nation's declining generation. This study aims to research the concept of education from the perspective of K.H. Muhammad Zaini bin Abdul Ghani and its relevance to contemporary Islamic education. The method used by researchers in this study is descriptive qualitative, with library research that makes documents or books the primary source of research. The data were analyzed using the Miles and Huberman analysis model: data condensation, data presentation, and data verification. The results showed that the education concept from the perspective of K.H. Muhammad Zaini bin Abdul Ghani has several components: purpose, curriculum, methods, educators, and students. The results show that education concept from the perspective of K.H. Muhammad Zaini bin Abdul Ghani is relevant to contemporary Islamic education. It is hoped that this research can contribute to the education concept that can be applied in contemporary Islamic education and can be an educational concept that can answer the problems of contemporary Islam.